THE ROLE OF INTERACTIVE DIGITAL GAMES IN ENHANCING ENGLISH LANGUAGE SKILLS IN PRESCHOOL CHILDREN - Choriyeva Xurmo (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
ABSTRACT: This article explores the role of interactive digital games in enhancing English language skills among preschool children. It examines how gamified learning experiences contribute to vocabulary acquisition, listening comprehension, speaking, and overall communicative competence. Emphasis is placed on age-appropriate design, engagement strategies, and the integration of play-based learning with digital tools. The findings provide practical recommendations for educators to use interactive digital games effectively, fostering motivation, cognitive development, and early foreign language proficiency in young learners.